Microglia is a Key Player in the Reduction of Stroke Damage Promoted by the New Antithrombotic Agent Ticagrelor. Issue 6 (June 2014) - Gelosa, Paolo; Lecca, Davide; Fumagalli, Marta; Wypych, Dorota; Pignieri, Alice; Cimino, Mauro; Verderio, Claudia; Enerbäck, Malin; Nikookhesal, Elham; Tremoli, Elena; Abbracchio, Maria P; Sironi, Luigi
The ADP-responsive P2Y12 receptor is expressed on both platelets and microglia. Clinical data show that ticagrelor, a direct-acting, reversibly binding P2Y12 -receptor antagonist, reduces total cardiovascular events, including stroke. In our present study, we investigated the expression of P2Y12 receptors and the effects of ticagrelor on brain injury in Sprague-Dawley rats subjected to a permanent middle cerebral artery occlusion (MCAo). Rats were treated per os with ticagrelor 3 mg/kg or vehicle at 10 minutes, 22, and 36 hours after MCAo and killed after 48 hours. Immunofluorescence analysis showed an ischemia-related modulation of the P2Y12 receptor, which is constitutively expressed in Iba1 + resting microglia. After MCAo, activated microglia was mainly concentrated around the lesion, with fewer cells present inside the ischemic core. Ticagrelor significantly attenuated the evolution of ischemic damage—evaluated by magnetic resonance imaging (MRI) at 2, 24, and 48 hours after MCAo—, the number of infiltrating cells expressing the microglia/monocyte marker ED-1, the cerebral expression of proinflammatory mediators (interleukin 1 (IL-1), monocyte chemoattractant protein 1 (MCP-1), nitric oxide synthase (iNOS)) and the associated neurologic impairment. In transgenic fluorescent reporter CX3CR1-green fluorescent protein (GFP) mice, 72 hours after MCAo, ticagrelor markedly reduced GFP + microglia and both early and late infiltrating blood-borne cells. Finally, in primary cultured microglia, ticagrelor fully inhibited ADP-induced Chemotaxis ( P <0.01). Our results show that ticagrelor is protective against ischemia-induced cerebral injury and this effect is mediated, at least partly, by inhibition of P2Y12 -mediated microglia activation and Chemotaxis.